Asas kebebasan berkontrak dan perlindungan konsumen dalam kontrak baku pada internet banking - Sagi Janitra; Mohammad Ghufron Az; Diah Aju Wisnuwardhani (Jurnal Cakrawala Hukum, 2021)
For customers, internet banking service facilities provide the advantage of being able to make online payments. Internet banking also provides accommodation for banking activities through computer networks anytime and anywhere quickly, easily, and safely because it is supported by a strong security system, especially for those who are always busy managing their finances. As for the formulation of the problem in this paper, how is the use of the principle of freedom of contract in standard contracts on internet banking seen from the point of view of Law Number 8 of 1999 concerning consumer protection and what is the legal protection for internet banking users for the contents of the standard contract? The result of this research is that the standard agreement on internet banking in its contents must be in accordance with the legal bases and articles that have been regulated in Law Number 8 of 1999 concerning Consumer Protection, where the agreement is not allowed if it harms the party implementing the agreement standard which in this case is a customer or debtor and the Bank is responsible for carrying out all obligations contained in the Banking Act, also in the Consumer Protection Act. The bank is also responsible for losses suffered by customers, whether they arise due to system errors or due to errors made by bank officers. A bank can only be released from its responsibilities after fulfilling its performance and paying compensation to the customer, or if the loss is due to the customer's fault or due to a compelling situation.How to cite item: Janitra, S., Ghufron Az, M., Wisnuwardhani, D. (2021). Asas kebebasan berkontrak dan perlindungan konsumen dalam kontrak baku pada internet banking. Jurnal Cakrawala Hukum, 12(3), 334-343. doi:https://doi.org/10.26905/idjch.v12i3.7361.